2020
DOI: 10.21203/rs.3.rs-23000/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence And Associated Risk Factors Of Bacterial Vaginosis Among Pregnant Women In Africa: A Systematic Review

Abstract: Background: Bacterial vaginosis is the most common form of vaginitis which causes abnormal vaginal discharge in woman of childbearing age, which predispose to various gynecological and obstetric problems. In Africa sub-continent, the prevalence of BV among pregnant women is different among different countries. This review aimed to show the overall prevalence and to describe the different risk factors associated with BV among pregnant women in Africa. Methods: PubMed, Medline, science direct, Google scholar and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“… 34 It is also more or less comparable with 24.8% pooled prevalence report of BV in Africa. 14 A similar study finding was also reported from Ethiopia, Addis Ababa of 19.4%. 17 This comparable sample size, method used and similarity of study population may contribute to the very close findings among different studies.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“… 34 It is also more or less comparable with 24.8% pooled prevalence report of BV in Africa. 14 A similar study finding was also reported from Ethiopia, Addis Ababa of 19.4%. 17 This comparable sample size, method used and similarity of study population may contribute to the very close findings among different studies.…”
Section: Discussionsupporting
confidence: 78%
“… 17 This comparable sample size, method used and similarity of study population may contribute to the very close findings among different studies. 14 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations